Forecasting Produksi dan Analisis Trend Harga Daging Ayam Broiler di Provinsi Bengkulu - Yurike, Yurike (BPFP Universitas Bengkulu, 2023)
Production forecasting and trend analysis of broiler meat prices need to be carried out to ensure that people, particularly in Bengkulu Province, have access to sufficient broiler meat to meet their nutritional needs. The study's objectives were to conduct a forecasting analysis or prediction of broiler meat output to fulfill community demands and to examine trends in broiler meat prices in the province of Bengkulu from 2012 to 2021. The method in this study is descriptive quantitative with the Secondary Data Analysis (SDA) approach in a time series and then analyzed through Microsoft Excel with the forecast method and described. The results showed forecasting of broiler meat production in Bengkulu Province showing a positive trend (increasing) and the trend of broiler meat prices was quite fluctuating with a positive trend. The government needs to encourage increased investment in broiler chickens and conduct outreach to breeders regarding good chicken maintenance so that broiler meat production continues to increase. When the availability of chicken meat is maintained, it is hoped that the price of chicken meat will be more stable. Additionally, with rising chicken meat production, Bengkulu Province is able to provide all of its residents' needs, negating the need for outside suppliers. Key words: Broiler meat, forecasting, price, production, trend ABSTRAK Forecasting produksi dan analisis trend harga daging ayam broiler perlu dilakukan untuk memastikan bahwa masyarakat, khususnya di Provinsi Bengkulu, memiliki akses daging ayam broiler yang cukup untuk memenuhi kebutuhan gizinya. Tujuan penelitian untuk melakukan analisis forecasting atau prediksi produksi daging ayam broiler untuk memenuhi kebutuhan masyarakat dan menganalisis trend harga daging ayam broiler di Provinsi Bengkulu dari tahun 2012-2021. Metode dalam penelitian ini adalah kuantitatif deskriptif dengan pendekatan Analisis Data Sekunder (ADS) secara time series lalu dianalisis melalui Microsoft Excell dengan metode peramalan forecast dan di deskripsikan. Hasil penelitian menunjukkan forecasting produksi daging ayam broiler di Provinsi Bengkulu menunjukkan trend yang positif (meningkat) dan trend harga daging ayam broiler cukup fluktuatif dengan kecenderungan yang positif. Pemerintah perlu mendorong peningkatan investasi ayam broiler dan melakukan sosialisasi kepada peternak mengenai pemeliharaan ayam yang baik agar produksi daging ayam broiler terus meningkat. Ketika ketersediaan daging ayam tetap terjaga, di harapkan harga daging ayam menjadi lebih stabil. Selain itu dengan produksi daging ayam yang cenderung meningkat maka Provinsi Bengkulu dapat memenuhi kebutuhan masyarakat akan daging ayam sehingga tidak perlu memasok dari luar Provinsi. Kata kunci: Daging ayam broiler, forecasting, harga, produksi, trend